PEMANFAATAN MEDIA ANIMASI TEMA DAUR HIDUP HEWAN PADA MATA PELAJARAN IPAS DALAM MEMBENTUK BERPIKIR KRITIS SISWA KELAS IV DI MI RAUDLATUS SHIBYAN - Zuhri, Nur Iklimah; Feriska Listrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The lack of interest of students in participating in Natural and Social Sciences (IPAS) subjects about the life cycle of animals in the form of the life cycle of butterflies is a problem in itself, it is influenced by monotonous learning methods where teachers tend to rely only on lecture methods, as a result students are less actively involved and not trained in developing critical thinking skills. coupled with the lack of use of learning media such as books and whiteboards, which are used conventionally without variety of methods, thus causing the learning atmosphere to become boring and making students lose enthusiasm in participating in learning activities in the classroom, The impact of this is the inhibition of the process of developing students' critical thinking skills, especially in science subjects. This research was conducted to provide stimulation and a positive impact in optimizing students' thinking processes in carrying out teaching and learning activities through a two-dimensional audio-visual method in the form of animation media. Qualitative research methods are research procedures that produce descriptive data in the form of written or spoken words from subjects or observable behaviors, this method emphasizes the context as a whole (holistic), using a humanistic approach. Based on the results and discussion of this research, animation media plays a very important role in increasing enthusiasm and forming students' critical thinking processes through two-dimensional audio-visual media, it will make it easier for each student to illustrate the material presented in the IPAS subject about the material of the life cycle of animals in accordance with the life cycle cycle of butterfly animals. Even the principal and teachers gave a very positive response in the implementation of animation media because it has the effectiveness in increasing enthusiasm, attention, and critical thinking towards students in carrying out learning activities in the classroom.